IMPLEMENTATION OF AN INTEGRATED GUIDED INQUIRY LEARNING MODEL FOR GENERIC SCIENCE SKILLS ON CHEMICAL EQUILIBRIUM MATERIAL - Pratiwi, Risa Oktavia; Ani Sutiani (Jurnal Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the effect of evaluating students initial knowledge and worksheets on learning outcomes and to determine the difference in learning outcomes between high initial knowledge and low initial knowledge using an integrated Guided Inquiry learning model of Generic Scinece Skills on Chemical Equilibrium material. This research used a dual paradigm design with two independent variables and one dependent variable. The population in this study were all students in class XI IPA at SMA Swasta Kartika I-2 Medan, which consisted of 4 classes. The sample in this study was taken using a purposive sampling technique from 1 class, namely XI IPA 1 which is taught using the Guided Inquiry learning model integrated with Generic Science Skills using learning tools consisting of evaluation of initial knowledge, teaching materials, student worksheets and evaluation of learning outcomes. The instrument used in this research were initial knowledge evaluation test instruments, learning outcomes evaluation test instruments, learning outcome evaluation test instruments, student worksheets and the non-test instruments used were student observation sheets. Data were analyzed using multiple linear regression tests and Independent Sample T-Test. The results of analysis of the data obtained show that there is a significant influence between the evaluation of students initial knowledge and worksheets on learning outcomes and there is a difference between students with high initial knowledge and worksheets on learning outcomes and there is a difference between students with high intial knowledge and students with low initial knowledge.